Aphanomyces invadans, the causal agent of Epizootic Ulcerative Syndrome, is a global threat to wild and farmed fish. Issue 3 (June 2018) - Iberahim, Nurul Aqilah; Trusch, Franziska; van West, Pieter
Abstract: Aphanomyces invadans is a eukaryotic pathogen and the causative agent of Epizootic Ulcerative Syndrome (EUS) in fish and is responsible for mortalities of up to 100% in aquaculture. A. invadans was first discovered in Japan in 1971, and since then it has been found in Australia, North America, Southern African countries and Asia. Methods for the correct identification of A. invadans are well established now and involve PCR-based detection and microscopy. However, the pathogenesis of A. invadans is poorly understood. Environmental stress (mainly temperature) and the associated immunocompromised fish seem to induce infections of A. invadans and outbreaks of EUS. Understanding the process of infection in more depth is fundamental for the discovery of novel effective treatments to combat the disease. In this review, we discuss morphological characteristics of A. invadans and its pathogenicity as well as various approaches of treatment.